2020
DOI: 10.1089/aid.2019.0278
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Hormones and Antiretroviral Exposure in Plasma, Cervicovaginal Fluid, and Upper-Layer Packed Cells of Malawian Women Living with HIV

Abstract: Overlap in metabolism pathways of endogenous female sex hormones and antiretroviral drugs may lead to altered exposure to these compounds. In a family planning clinic in Lilongwe, Malawi, blood, blood cell, and cervicovaginal fluid (CVF) samples from seventy-three HIV positive Malawian women taken in follicular and luteal menstrual phases were assessed for estradiol and progesterone by chemiluminescent immunoassay, and for antiretroviral concentration by liquid chromatography-mass spectrometry. In both follicu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…In a recent ex vivo study, DMPA was found to suppress TAF metabolism in female genital tract cells although little or no effect was seen in blood cells ( Shen et al, 2017 ). Recent clinical evaluations of TFV-based regimens also indicated that mucosal tissue TFV-DP may be affected by exogeneous hormonal treatments, but not by endogenous hormonal cycles ( Cottrell et al, 2019 ; Nicol et al, 2020a , 2020b ).…”
Section: Introductionmentioning
confidence: 99%
“…In a recent ex vivo study, DMPA was found to suppress TAF metabolism in female genital tract cells although little or no effect was seen in blood cells ( Shen et al, 2017 ). Recent clinical evaluations of TFV-based regimens also indicated that mucosal tissue TFV-DP may be affected by exogeneous hormonal treatments, but not by endogenous hormonal cycles ( Cottrell et al, 2019 ; Nicol et al, 2020a , 2020b ).…”
Section: Introductionmentioning
confidence: 99%